Implementación de un Sistema de Control de Vuelo Automático para un Vehículo Aéreo no Tripulado (UAV) - Rodríguez-León, Leonardo (Instituto Tecnológico de Costa Rica, 2015)
The problem of erosion is very common in Costa Rica's soils. The soil loses fertility which affects agricultural activities, and this problem also affects water resources because it gets contaminate through sediments. Through time the human beings have created different methods to quantify the erosion process to reduce the presence of this problem, one of the most used methods is the runoff plots which are portions of land bounded by walls, which remain under observation to monitor the progress of erosion. The runoff plots are an expensive method because of its construction and maintenance, and it also turns out to be ineffective because they provide low valid information. That problem has motivated a research initiative between the Costa Rica Institute of Technology and the PRIAS Laboratory of CeNAT with the purpose of quantifying and modeling erosion by using UAV (Unmanned Aerial Vehicles) systems dedicated to photogrammetry work. The idea is that these systems measure physical variables and georeferenced images to reconstruct maps of the ground in high resolution to quantify the erosion process automatically at a given time. In this project, we develop the implementation of an autopilot flight control system for an UAV system, which is able to follow automated flight routes programmed from a computer using a specialized software platform and get the flight data for further processing of georeferencing of images.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2015.
Keywords: Fotogrametría; Sistemas de control; Plataformas; Software; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics::Electronics